Joint Fountain Codes and Network Coding for Wireless Butterfly Networks - Di, Xiaofei; Xiong, Ke; Zhang, Yu; Qiu, Zhengding; Zhong, Zhangdui (Elektronika ir Elektrotechnika, 2014)
The wireless butterfly network is a representative model for multi-source multi-destination relay communication scenario, where opportunistic network coding (ONC) can be deployed to improve the system’s throughput. However, ONC requires feedback information and this may deteriorate the throughput performance and counteract the advantage of ONC. To this end, in this paper, we firstly propose a new transmission protocol by combing fountain codes and network coding into the transmission strategy design for wireless butterfly network. Then, we formulate and analyse the throughput performance for the proposed protocol. Finally, numerical and simulation results are presented, which shows that our proposed protocol outperforms traditional ONC scheme. DOI: http://dx.doi.org/10.5755/j01.eee.20.2.3954